Post Covid Era and the Influence of Online Healthcare Platforms on the Health-Seeking Behaviour of Adults - Keerthana Venkatesan; Prabakar S (Asia Pacific Journal of Health Management)
Need & Objectives of the study: Good living conditions include basic shelter, food, and clothing but the aspect of access to quality healthcare has become one of the essentials of livelihood, especially in this post-covid era. The post covid era has also marked the digital evolution where the role of social media is inevitable to a wider range such that it has acquired the position among the social institutions influencing diverse population on all aspects due to its multiple users. This multiplicity of users has demanded the interference of social media in all spheres of life even in the field of health and medicine. It has opened up new ways of access for sharing information and social support, due to increased connectivity and direct participation bringing changes in the illness behavior.